El Cementerio General de La Apacheta: Un análisis multidimensional de su rol en Arequipa. - Cjuro-Gutierrez, Luis Enrique; Oroza-Villegas, Consuelo; Bedregal-Alpaca, Norka (Revista: Módulo Arquitectura CUC)
The General Cemetery of La Apacheta is considered one of the oldest and most important cemeteries in the city of Arequipa, which has allowed it to accumulate great historical, cultural, architectural, artistic, mysterious and spiritual wealth. This article analyses this cemetery as a multidimensional public space, exploring five dimensions: liminality, spirituality, commerciality, multiculturality and multifunctionality. With a qualitative approach, using documentary analysis, observation and interview techniques, the interaction between these dimensions is analysed. Tension is observed between heritage preservation and social inclusion, as well as challenges in economic management and the lack of comprehensive urban planning. The study concludes that La Apacheta has a high potential as a public space, but requires strategic management that balances the preservation of its spiritual character and the integration of new functions, improving accessibility, economic sustainability and urban planning that recognises its historical and cultural value.